Hygroscopic movements of cone scale of white fir Abies concolor are tuned by quantitative variation of the scale Bauplan - Wiczołek, Łukasz; Wodniok, Wiktoria; Borowska-Wykręt, Dorota; Nowak, Anna; Arkorful, Emmanuel; Łyczakowski, Jan J.; Kwiatkowska, Dorota (Frontiers in Plant Science, 2025)
Seed cones in gymnosperms consist of scales composed of dead cells at maturity. In Abies concolor, seed release occurs when entire seed-scale complexes, including sterile bracts that support the ovuliferous scales, are shed, causing the cone to disintegrate. This process is driven by the hygroscopic movements of the scales, which result from the reversible and uneven deformation of dead tissues in response to changes in water content. Unlike pine seed cones, which serve as a model for scale movement studies, fir features large, lamina-like ovuliferous scales that undergo extensive movements, including significant changes in surface area and profound shape transformations. Therefore, the objective of this study was to elucidate the mechanism of scale movement in fir. Quantification of surface deformation of the scale lamina and isolated tissues during transitions between dry and wet states revealed significantly higher deformation of abaxial than adaxial scale surface. Analysis of scale anatomy and chemical composition of cell walls identified three plate-shaped building blocks of the lamina: a relatively loose adaxial plate; a plate including vascular bundles built of thick-walled xylem fibers, with walls rich in xylosyl residues; an abaxial plate rich in mannosyl residues and comprising scattered sclerenchyma fibers and compact epidermis. Mechanical damaging of lamina surface and dissection of individual plates showed that lamina actuation is resilient and lamina movements are driven by interplay between the three plates. The relative plate contribution to the lamina volume tunes the extent of hygroscopic movements. In particular, different contribution of the adaxial plate to the scale thickness and related asymmetry of position of vascular bundle plate explain the profound discrepancy in the degree of scale bending despite the similarities in tissue structure, chemical composition and surface strains of individual scales. We postulate that the hygroscopic movements are tuned by simple quantitative modifications of the lamina Bauplan.